Improving Identification and Child-Focused Collaborative Care for Children of Parents With a Mental Illness in Tyrol, Austria - Christiansen, Hanna; Bauer, Annette; Fatima, Batool; Goodyear, Melinda; Lund, Ingunn Olea; Zechmeister-Koss, Ingrid; Paul, Jean Lillian (Frontiers in Psychiatry, 2019)
Background: Children of parents with a mental illness (COPMI) are more likely to experience negative long-term adversities. However, interventions to support their needs early can significantly enhance adjustment and reduce negative outcomes. Approximately one in four children currently lives with a parent with mental illness worldwide. The lifelong impact for individuals, governments, and broader society is likely to be substantial. There are significant workforce barriers to the early identification of COPMI and addressing their needs, particularly within the adult mental health care system. The current study aims to reduce such barriers and to improve identification of COPMI in the current health care systems. Objectives: The project “The Village” is a multidisciplinary health and social care policy intervention and seeks to improve child development and well-being outcomes for children of parents with a diagnosed mental illness. This will be achieved through the co-development, implementation, and evaluation of a practice approach to the early identification and collaborative care for COPMI, through establishing child-focused support networks. This will be done with open innovation science (OIS) approaches engaging the public in Tyrol, a geographical region of Austria, throughout 4 years. As part of the co-development process, we will work with stakeholders to co-develop the practice approaches based on evidence-based approaches and determine the most appropriate study design to evaluate those, as well as the implementation processes we will undertake. Methods: The project is underpinned by theories from different disciplines (i.e., public health, psychology, sociology, linguistics, economic sciences) as well as drawing on different approaches (i.e., co-development, implementation science, symbolic interactionism, and realist evaluation). It is based on the seven content work packages (WPs): 1) management, 2) focusing on children and methods to understand their “voice,” 3) scoping, 4) co-development, 5) implementation, 6) evaluating the practice approaches, and 7) knowledge dissemination. “Scoping” will involve exploring the existing evidence, practice, and current state of identification and collaborative care in Tyrol, Austria. “Co-development” involves the co-design of practice approaches to identify and support children in partnership with key stakeholders and service providers working in Tyrol. The “implementation” of practice approaches will be based on the results of the co-development phase and will involve working with organizations to develop support strategies that draw on known organizational drivers from the field of implementation science to support the rollout of the practice approaches. In “Evaluation” we will follow principles of a realist approach; this includes developing program theories and logic models for the practice approaches. Those will set out the outcomes hypothesized to achieve and the processes that are expected to lead to those changes. This will refer to changes in children, parents, and practitioners. We expect that the main focus will be on measuring child quality of life and mental health outcomes, and outcomes that are on the path to those (such as social support needs, resilience, mental health literacy, stigma, and help-seeking behavior) as well as costs. The “child voice” WP focuses on children’s perceptions and needs as the importance of “assent” and support of children to develop their own “voice” in health care is increasingly recognized within child health research. The “dissemination” step focuses on reaching a broad public audience of different stakeholders, researchers, and families involved. Discussion: The research project aims to directly improve identification and support of vulnerable children across selected regions in Tyrol, Austria, and by doing so, improve the health and well-being of future generations, through breaking the cycle of intergenerational transfer of adverse childhood experiences.